Epidemiological determinants and magnitude of calf morbidity and mortality in Bahir Dar milk-shed, north west Ethiopia - Ferede, Y. (Addis Ababa University, 2015)
Herd level cross-sectional and calf level longitudinal observational study was conducted between November 2014 to April 2015 in peri-urban and urban dairy farms of Bahir Dar milk-shed, Ethiopia. The aims of this study were therefore, to determine the incidence rate of calf morbidity and mortality, investigating potential determinant factors of calf morbidity and mortality and to determine the passive transfer of immunity in some selected dairy calves. Both concurrent and prospective cohorts were employed to recruit calves aged below 6 month in the study herds. A total of 440 calves, a random sample of 322 calves from small-holder and 118 from five large dairy farms located in Bahir Dar milkshed were included in the study. Each study calf was individually ear -tagged and regularly monitored in monthly basis for clinical health problems up to an age of six months. Information on different potential risk factors was collected by using herd and calf level recording sheets and personal observations. Serum samples were taken from some study calves to determine their level of passive transfer and it was conducted in Bahir Dar Animal Health Diagnostic and Investigation Laboratory. The overall incidences of crude morbidity and crude mortality rates found in this study were 47.3% and 17.9%, respectively. Calf diarrhea, pneumonia, navel ill, septicemic conditions, Lumpy Skin Disease, rabies, congenital problems and other miscellaneous cases were encountered during this study. The most frequent disease condition was calf diarrhea with the incidence rate of 25.2% followed by pneumonia (8.6 %). The incidence of crude mortality was apparently higher in large sized dairy farms than smallholder farms. However, calf diarrhea and crude morbidity rates were higher in the latter. About six, 6, 4 and 2 explanatory variables were found significantly associated with crude mortality, crude morbidity, diarrhea and pneumonia respectively by multivariate Cox - regression at P<0.05. Older calves above three months age were at lower risk (HR=0.03, P=0.000) of mortality than younger calves of below three month. The relative hazard (HR=0.15, P=0.000) of mortality in good vigored calves was lower than that of calves with poor vigor at birth. Those calves fed complete colostrum were found at lower risk (HR=4.64, P=0.000) of mortality than those fed partial colostrum. Birth type (twin vs. single), method of colostrum feeding and farming system were also the other risk factors determining calf mortality. Likewise, older calves were found at lower risk of crude morbidity (H=0.45, P=0.000) than younger calves. The hazard of morbidity in those good vigored calves at birth was lower (HR=0.26, P=0.000) than calves with history of poor vigor. Furthermore, dam age, dam birth related disorders and study location were also found additional risk factors of crude calf morbidity. The relative hazard of diarrhea in crossbred calves (HR=2.63, P=0.016) was higher than that of local counter parts. Those good vigored calves at birth were also found at lower risk (HR=0.24, P=0.000) of diarrhea than that of poor vigored counter parts. Furthermore, calf age and study location were found to be additional risk factors of calf diarrhea. Those calves with previous treatment history were at greater risk (HR=0.076, P=0.000) for pneumonia than calves which did not receive any previous medical treatment. Moreover, vigor status at birth (HR=0.24, P=0.000) was found significantly associated with calf pneumonia. Out of 46 calves examined by Zinc sulfate (ZnSo4.7H20) turbidity test, about 8.7% of them were found with no detectable colostral Ig (FPT), the remaining 34.8% and 56.5% were found with adequate and partial protection levels, respectively. Generally, 65.2% of calves were found immunologically unprotected in the study herds. In conclusion, the incidence of calf morbidity and mortality found in this study were high and above economically tolerable level. This record therefore, could affect the productivity of the dairy farms through mainly decreasing the availability of replacement stock. Among the significant risk factors investigated, calf vigor, age, breed, dam age and amount of colostrum ingestion were found very important determinant factors of calf mortality and morbidity under the context of small-holder farming system in Bahir Dar milk-shed. A sound dairy calf management practice, is therefore needs understanding and manipulating of the above mentioned calf health determinant factors with subsequent application of tailor-made interventions.